The Feasibility of Conducting Pronunciation Instruction Using Musical Notation - SO, Wai Lun Valiant (The bulletin of Kaichi International University, 2022)
Language and music have been associated for hundreds of years. In fact, language instructors and institutes encouraging language learners to study music for language learning can often be observed. However, actual studies about the correlation between the two are scarce. Are language and music truly correlated? Can studying music promote language learning? This paper attempts to search for the answers to these questions by investigating the correlation between pronunciation and music, and by examining whether making use of musical notation to aid pronunciation instruction is a logical and feasible approach. A brief introduction of some common pronunciation instruction methods, challenges instructors may face while conducting these methods, previous studies about the relationship between pronunciation and music, and theoretical models of intonations, syllables, and stress instruction using musical notation will be the main topics of this paper. Considering the ongoing COVID-19 pandemic, this study temporarily restricts the writer to being the only test subject and serves the purpose of being the basis of future studies about pronunciation instruction and musical notation.